Changing the paradigm in health and care services: modern value chains using open innovation for the creation of new digital health solutions - Carrilho, Joana; Videira, Diogo; Campos, Cláudia; Midão, Luis; Costa, Elísio (Frontiers in Digital Health, 2023)
Digital Health is a subject of extensive discourse when considering its current and future significance. This significance arises from a convergence of various factors, including the escalating capabilities and cost-effectiveness of computing and communication technology, coupled with the mounting demands and challenges faced by healthcare systems. The integration of health and technology, when studied collectively with the purpose of addressing tangible real-world issues, holds the potential to generate substantial outcomes that greatly influence the provision of clinical and social care, thereby enhancing the overall well-being of both individuals and populations. In this sense, in this paper we propose a collaborative approach, using Open Innovation, where the most relevant stakeholders—health and care professionals, citizens and companies—work together to develop and validate innovative digital solutions for health and care. We have called this approach of value co-creation the Collaborative Ecosystem, and we focus specifically on the potential development of the Regional Ecosystem for Collaborative Innovation in Digital Health and Care, and the envisioned implications of its implementation in economic and social dimensions.